Analytical Study of the tobacco crop support policy in Lattakia - يعقوب , غسان; عليو , محمود; عمران, اسماعيل (Latakia University Journal -Biological Sciences Series, 2020)
This research aimed to study the government subsidies for tobacco crop in Lattakia, aiming to evaluation to the supported plans, and to determine the extent to which farmers benefit from government subsidies and its effect for increasing the production, and the planted lands, the research depended upon hypotheses that the support policy is facing shortage in its connection to growth tobacco crop. Data were collection from primary sources in questionnaires where 370 questionnaires were distributed using simple random sampling method, and secondary sources represented in references, reports, books, websites. The study used descriptive analytical method, and the data were analyzed using (SPSS20). The results of the research showed the decrease of support which is given to the tobacco crop, and high cost for its production , in addition to small planted sizes, and this leaded to decrease the expansion in the tobacco crop agriculture, and this research leaded to late support for (pesticides , seeds, sacks) , and not getting it on time, in addition to limited prices for buying it which are not suitable for most of the tobacco's farmers for decrease for both prices support, and farmer benefits, and this will be less for the main purpose of the support politics which is represented in increasing the average of growing crops and achieving agricultural development.